Implementation of Infrastructure Development Program in Flood Handling in Medan Selayang District, Medan City - Siregar, Andi Mario; Harahap, R. Hamdani; Ridho, Hatta (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study examines the implementation of infrastructure development in flood management in Medan Selayang District, Medan City. Medan Selayang, being one of the flood-prone areas in the city, faces significant challenges due to rapid urbanization, inadequate drainage systems, and poor waste management. The objective of this research is to assess the effectiveness of infrastructure interventions, such as the construction of drainage channels, flood retention ponds, and river embankments, in mitigating flood risks and improving public resilience. Data collection was conducted through field observations, interviews with local authorities and community members, and analysis of flood occurrence records. The results indicate that while there has been notable progress in infrastructure development, challenges remain in terms of the sustainability and maintenance of these systems. Issues such as insufficient funding, lack of coordination between stakeholders, and limited public awareness of flood prevention measures have hindered the optimal functioning of flood management infrastructure. This study emphasizes the need for integrated planning, enhanced community participation, and continued investment in infrastructure to effectively address flood risks in Medan Selayang. The findings provide valuable insights for policymakers and urban planners in designing more resili.